2013
DOI: 10.1177/0956797613492775
|View full text |Cite
|
Sign up to set email alerts
|

When Truth Is Personally Inconvenient, Attitudes Change

Abstract: A naturalistic investigation of New Jersey residents, both before and after they experienced Hurricanes Irene and Sandy, examined support for politicians committed or opposed to policies designed to combat climate change. At Time 1, before both hurricanes, participants showed negative implicit attitudes toward a green politician, but at Time 2, after the hurricanes, participants drawn from the same cohort showed a reversed automatic preference. Moreover, those who were significantly affected by Hurricane Sandy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 26 publications
1
45
2
1
Order By: Relevance
“…Several empirical studies have found that the past experience of adverse climate phenomena can influence levels of knowledge and attitudes related to climate change and other environmental issues [15][16][17]. However, Whitmarsh [5] has found the opposite empirical result, that is, flood victims and non-victims have the same level of understanding of climate change.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several empirical studies have found that the past experience of adverse climate phenomena can influence levels of knowledge and attitudes related to climate change and other environmental issues [15][16][17]. However, Whitmarsh [5] has found the opposite empirical result, that is, flood victims and non-victims have the same level of understanding of climate change.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Associated weather events range from slight temperature changes to extreme storms. Humans are capable of perceiving even minor temperature changes and increase 555 their intentions to act after being exposed to extreme weather events (Broomell, Budescu, & Por, 2015;Rudman, McLean, & Bunzl, 2013;Spence et al, 2011). We argue that perceptions of these local climate change-associated weather events are guided by top-down processes, modulated by political identity.…”
Section: A Perceptual Model Of Identity-based Climate Change Judgmentsmentioning
confidence: 88%
“…For example, people who are more knowledgeable about climate change and the causes of climate change are generally more concerned about climate change (Sunblad et al, 2009;Tobler et al, 2012;Guy et al, 2014). People with direct experiences of consequences related to climate change are more concerned about problems related to climate change, and more willing to reduce their energy use (Spence et al, 2011;Akerlof et al, 2013;Rudman et al, 2013). Individuals with right-of-centre political views and those who emphasize individual autonomy rather than collective ties are more likely to reject mainstream climate science knowledge (Kahan et al, 2010;.…”
Section: Knowledgementioning
confidence: 99%